Exploring School Engagement and Academic Outcomes Over Time: The Role of Contextual Factors in Chile - Saracostti, Mahia; Miranda, Edgardo; Guzmán, Paulina; Schnettler, Berta; Concha‐Salgado, Andrés; Toro, Ximena; Lara, Laura; Suazo, Iván (Psychology in the schools, 2025)
ABSTRACT School engagement is a multidimensional construct encompassing affective, cognitive, and behavioral dimensions, influenced by contextual factors like family, peer, and teacher support. This longitudinal study examines how these dimensions of school engagement mediate the relationship between contextual factors and academic outcomes—specifically, class attendance and performance in language and mathematics—over 3 years among 284 Chilean students (46.5% boys and 53.5% girls) enrolled in their first year of secondary education in public schools in Chile. Our findings reveal that teacher support plays a significant role in enhancing school engagement, which in turn impacts academic outcomes, with behavioral and cognitive engagement having distinct effects on attendance and subject performance. The study also identifies gender differences in engagement dynamics, with teacher support influencing affective engagement in girls and behavioral engagement in boys. This study addresses a gap in longitudinal studies within Latin America, providing insights into the complex interplay between contextual factors, gender, and school engagement, with implications for targeted educational interventions. Summary Teacher support emerged as a crucial factor in fostering school engagement, with significant effects on behavioral and cognitive engagement, highlighting the need for professional development programs that equip educators with strategies to strengthen Student–teacher relationships. The distinct impact of engagement dimensions on academic outcomes underscores the importance of targeted interventions, with behavioral engagement playing a key role in mathematics and language performance. In contrast, cognitive engagement specifically enhances language achievement. Gender differences in school engagement reveal the need for tailored educational strategies, as teacher support influences affective engagement in girls and behavioral engagement in boys, emphasizing the importance of gender‐responsive approaches in fostering student success.